1964
DOI: 10.1080/00288233.1964.10416384
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and microbial growth in a New Zealand grassland soil

Abstract: C02 evolution from re-moistened, air-dried Craigieburn fine sandy loam variously treated with glucose and mineral supplements showed that available carbon was more limiting to microbial activity in this soil than were mineral nutrients. Direct observation of the soil population developing in these experiments showed a pattern which varied little with treatment and which indicated that bacteria with a rod-coccus life cycle were active under the conditions of the experiments. Limited observations of bacteriophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
1972
1972

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The overall nitrification and nitrogen mineralisation eJfects of liming which are inferred from Tables 2 and 3 are in keeping with earlier field and laboratory studies of this soil by O'Connor et al (1962). Robinson (1963), and Robinson and Macdonald (1964).…”
Section: Phasementioning
confidence: 99%
“…The overall nitrification and nitrogen mineralisation eJfects of liming which are inferred from Tables 2 and 3 are in keeping with earlier field and laboratory studies of this soil by O'Connor et al (1962). Robinson (1963), and Robinson and Macdonald (1964).…”
Section: Phasementioning
confidence: 99%
“…) showed that nitrogen was mineralised to a greater degree than sulphur. Because the level of respiratory activity in the Craigieburn soil in the unimproVed state is low (Robinson and MacDonald 1964). any effect of cultural practice on mineralisation would probably be small.…”
Section: Influences Of Ground Treatment On Sulphur Availabilitymentioning
confidence: 99%